THE NATURE OF THE ATHEISTIC PROPAGANDA SYSTEM OF THE COMMUNIST IDEOLOGY AND ITS CHARACTERISTICS IN NATIONAL TERRITORIES - Djumaev Bekzod Boymurad ugli (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
The article analyzes the information related to the attitude of the Soviet government to religion and its violent policy and persecution of religious people from a historical point of view based on reliable sources.